Face-Threatening Acts Performed by Joe Gardner in Soul Movie - Clarissa Lievany Budianto; Sang Ayu Isnu Maharani; Made Detriasmita Saientisna (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
Speech acts are actions carried out through language that do more than just share information; they can also affect the listener or change social situations. Sometimes, these spoken interactions may cause the listener to feel uncomfortable or lose respect. The idea of protecting a person’s dignity and social standing in communication is known as ‘face.’ When speech acts threaten this sense of face, they are called face-threatening acts. This study aims at identifying and analyzing the face-threatening acts performed by the character Joe Gardner in Pixar’s animated movie Soul (2020), by applying Brown and Levinson’s (1987) framework. Data were collected using the documentation method and note-taking technique, focusing on Joe Gardner’s utterances throughout the movie. The analysis employs a descriptive qualitative method, involving classification, identification, and verification based on the four types of face-threatening acts. The findings show that Joe Gardner performs all four types of face-threatening acts in 103 utterances: threatening the hearer’s negative face (61.2%), threatening the hearer’s positive face (23.3%), threatening the speaker’s negative face (6.8%), and threatening the speaker’s positive face (8.7%). The most frequently used type is the threat to the hearer’s negative face.